Report on scientific cod fishing and monitoring in 2023 in Åland, Finland - Raitaniemi, Jari; Leskelä, Ari (Luonnonvarakeskus, 2025)
At present, Eastern Baltic cod (Gadus morhua) in the southern Baltic Sea grows slowly, shows low condition factor and is heavily infected by the larvae of liver worm (Contracaecum osculatum). It has been hypothesized that either the heavy infection by liver worms, lack of suitable food due to lack of oxygen in the deep bottoms of the Baltic Sea or both together cause severe problems for the cod. The final host of the liver worm is grey seal (Halichoerus grypus), and the worm is carried to cod via prey, smaller fish. There is a small-scale cod fishery in the Finnish waters in the Sea of Åland, where cod are large sized and in good condition. Grey seals are abundant in these waters. In this study, the occurrence of Contracaecum larvae in the livers of cod especially in the Sea of Åland and the prey of the cod in the year 2023 were examined and presented together with the results from the years 2020, 2021, and 2022. The size of measured cod in 2023 varied from 30 to 118 cm (total length). Similarly, as in 2020–2022, the number of Contracaecum osculatum larvae on liver surface correlated with cod length. The Fulton’s condition factor of the cod in all years was high (1.01–1.13 in Åland). More importantly and similarly as in the previous years, the condition of the cod was not found to be in a statistically significant relation to the number of Contracaecum larvae on the liver surface nor the number of larvae per liver weight. The most common food items were Saduria and clupeid fish. The samples from all three years support the conclusion that when there is enough food for the cod, the effects of Contracaecum osculatum infection on the condition and growth of cod are small or even insignificant.
Keywords: Gadus morhua; Cod; Contracaecum osculatum; Hangö; liver worm; the Baltic Sea; the Sea of Åland